Recent Advances in Liver Engineering With Decellularized Scaffold - Dai, Qingqing; Jiang, Wei; Huang, Fan; Song, Fei; Zhang, Jiqian; Zhao, Hongchuan (Frontiers in Bioengineering and Biotechnology, 2022)
Liver transplantation is currently the only effective treatment for patients with end-stage liver disease; however, donor liver scarcity is a notable concern. As a result, extensive endeavors have been made to diversify the source of donor livers. For example, the use of a decellularized scaffold in liver engineering has gained considerable attention in recent years. The decellularized scaffold preserves the original orchestral structure and bioactive chemicals of the liver, and has the potential to create a de novo liver that is fit for transplantation after recellularization. The structure of the liver and hepatic extracellular matrix, decellularization, recellularization, and recent developments are discussed in this review. Additionally, the criteria for assessment and major obstacles in using a decellularized scaffold are covered in detail.